Calcium and gibberelic acid influence on in vitro adventitious elongement of Eucalyptus globulus - Calderon-Baltierra, Ximena V. (Bosque (Valdivia), 1994)
The ex vitro establishment of Eucalyptus globulus plantlets obtained by in vitro micropropagation is successful only when elongement is achieved before rooting. In order to know the role of calcium and gibberelic acid (GA3 ) in the elongement of adventitious shoots these were grown on Murashige and Skoog medium (MS) and modified as follows: calcium full strength (440 mg/l) half strength (220 mg/l) and fourth strength (110 mg/l); GA3, 0.1 and 0.5 mg/l. A combination of MS with a normal concentration of calcium (440 mg/l) and 0.5 mg/l of GA3 resulted in a good development of roots. However leaves suffered a notorious deformation. It is recommended to use a lower concentration of GA3 (0.1 mg/l) in combination with a treatment of short dark periods.